2018
DOI: 10.3389/fimmu.2018.00468
|View full text |Cite
|
Sign up to set email alerts
|

Pretransplant IgA-Anti-Beta 2 Glycoprotein I Antibodies As a Predictor of Early Graft Thrombosis after Renal Transplantation in the Clinical Practice: A Multicenter and Prospective Study

Abstract: BackgroundGraft thrombosis is a devastating complication after renal transplantation. We recently described the association of anti-beta-2-glycoprotein-I (IgA-ab2GP1) antibodies with early graft loss mainly caused by thrombosis in a monocenter study.MethodsMulticenter prospective observational cohort study.Setting and participantsSeven hundred forty patients from five hospitals of the Spanish Forum Renal Group transplanted from 2000 to 2002 were prospectively followed-up for 10 years.OutcomesEarly graft loss a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 38 publications
1
13
0
Order By: Relevance
“…Identification by the antibodies of the IgA isotype of these zones of the molecule previously described in aPL of consensus and clearly related with the clinical signs of APS in animal models reinforces the findings in prospective studies of the strong association of the presence of these antibodies with the occurrence of APS events (11, 13, 38).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Identification by the antibodies of the IgA isotype of these zones of the molecule previously described in aPL of consensus and clearly related with the clinical signs of APS in animal models reinforces the findings in prospective studies of the strong association of the presence of these antibodies with the occurrence of APS events (11, 13, 38).…”
Section: Discussionsupporting
confidence: 83%
“…IgA anti-B2GP1 has been shown to be strongly associated with DVT and stroke (10) and the thrombogenic effects of IgA anti-β2GP1 antibodies in vitro and in vivo animal models has been shown (11). Along this line our group shown that the presence of IgA anti-B2GP1 was strongly associated with thrombosis in various situations including: thrombosis in hemodialyzed patient (12), graft-thrombosis after kidney transplantation (13), and thrombosis and mortality after heart transplantation (14).…”
Section: Introductionmentioning
confidence: 86%
“…Patients with CDK positive for IgA aB2GP1 who received a kidney transplant showed a greater incidence of early graft loss, mainly due to thrombosis (14,15). This fact has been confirmed in a prospective multicenter study (16).…”
mentioning
confidence: 61%
“…The diagnosis of allograft thrombosis was consistently biopsy proven (11,14,15,23,(25)(26)(27)(28)(29)(30)(31) and occasionally supported by renal ultrasound or radionuclide scanning before biopsy (18).…”
Section: Allograft Thrombosismentioning
confidence: 99%